The effects of spice blends in an apple-based extruded cereal-like product: maximizing flavor and health - Bell, Brandon Eugene (Kansas State University, 2009)
The potential health benefits of spices, used as flavor enhancers since ancient times, are being explored more and more by researchers in animal and in vitro models. The application of mood and emotion constructs to understand the consumer psyche is a relatively new area of study in food science. The main objective of our study was to determine if spices (a blend of cinnamon, ginger, nutmeg, and cloves) that have high antioxidant properties evoke/change emotions in consumers. The carrier food, an extruded apple-based cereal-like product, was selected because cereals are convenient and consumed by many. Three cereal-like products containing 0, 4, or a 5% spice blend were extruded at Kansas State University. Four consumer tests, one day of hedonic and just-about-right evaluations (n= 100), followed by three days of emotion testing were carried out. For the emotion tests, 25 consumers saw the control sample three times, 25 consumers saw the 4% blend sample three times, 25 consumers saw the 5% blend sample three times, and 25 consumers saw all three samples once. In a clinical trial (n=10), total antioxidant capacity and blood glucose levels were determined from two samples (control and the 4% blend). The data were subjected to analysis of variance and principal components analysis to determine significant effects and trends in the data, respectively. ‘Calm’ was the only emotion that was significantly different in all three samples, which decreased over time (pre-consumption to 1-hour post consumption). The emotion ‘Satisfied’ increased significantly in the 5% blend showing that there might have been an effect because of the higher spice content. The PCAs showed that for the 4% and 5% blends, the movement of the consumers was towards emotions such as active, energetic, and enthusiastic. There were no trends for the control. For the clinical trial, the 4% blend was significantly higher (P < 0.05) in total antioxidant capacity than the baseline, although the differences in absolute terms are debatable. Blood glucose levels were not significantly different. Future research needs to be done to better understand how individual emotions affect overall liking and product acceptance.
Keywords: Emotion; Spice; Clinical; Sensory; Extruded; Agriculture, Food Science and Technology (0359)